APPLICATION OF COMPLEX OF GEOPHYSICAL METHODS TO RISE PROGNOSIS RELIABILITY OF OIL AND GAS DEPOSITS IS THE NORTHERN SIDE OF DNIEPER- DONETSK DEPRESSION - SOROKIN, O.; SLOBODIANIUK, S.; SIRCHENKO, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
Authenticity prediction of hydrocarbons deposit, at the searches and exploring of hydrocarbons reservoirs by geophysical methods, relies on informing of every method in concrete geological condition and is characterized by the factor of definiteness 0<FD<1. Application complex of geophysical methods for study allows comprehensively the geological structure of perspective objects. Conformity scales and methods of investigation provide plenitude of authentic information about the structure, composition and condition of geological space. For the sure prediction of geological section (factor of definiteness more than 0,9) it is necessary to have coordination from 4 to 8 independent parameters of different geophysical fields. It provides the successful coefficient of the exploring well drilling within the limits of 0,62 – 0,8.